3D RuO2 Microsupercapacitors with Remarkable Areal Energy. (30th September 2015) - Ferris, Anaïs; Garbarino, Sébastien; Guay, Daniel; Pech, David
Abstract : Large areal capacitance electrodes made of ruthenium oxide on highly porous gold current collectors are realized by an attractive approach. The hybrid structure exhibits a capacitance in excess of 3 F cm −2 and an areal energy density for all‐solid‐state microsupercapacitors that is comparable to those of microbatteries.